2015
DOI: 10.1038/ncomms7286
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a ciliary margin-like stem cell niche from self-organizing human retinal tissue

Abstract: In the developing neural retina (NR), multipotent stem cells within the ciliary margin (CM) contribute to de novo retinal tissue growth. We recently reported the ability of human embryonic stem cells (hESCs) to self-organize stratified NR using a three-dimensional culture technique. Here we report the emergence of CM-like stem cell niches within human retinal tissue. First, we developed a culture method for selective NR differentiation by timed BMP4 treatment. We then found that inhibiting GSK3 and FGFR induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
369
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(391 citation statements)
references
References 66 publications
22
369
0
Order By: Relevance
“…Furthermore, the timing of neural differentiation seems to be species-specific, as seen in vivo, as illustrated by the slower neural maturation of hESCs compared with primate ESCs (Otani et al, 2016) and by the faster in vitro differentiation of mouse cells into neurons compared with human cells (Wichterle et al, 2002). In the case of the optic cup discussed earlier, it took much longer to form organoids from human cells than from mouse cells (Kuwahara et al, 2015), again reflecting the relative developmental timing of these species. One is tempted to speculate that timing is independent from one tissue to another, supported by the observation that developmental compensation time in the mouse is not the same for each organ, as discussed above (Kojima et al, 2014).…”
Section: Size Control and Scalingmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the timing of neural differentiation seems to be species-specific, as seen in vivo, as illustrated by the slower neural maturation of hESCs compared with primate ESCs (Otani et al, 2016) and by the faster in vitro differentiation of mouse cells into neurons compared with human cells (Wichterle et al, 2002). In the case of the optic cup discussed earlier, it took much longer to form organoids from human cells than from mouse cells (Kuwahara et al, 2015), again reflecting the relative developmental timing of these species. One is tempted to speculate that timing is independent from one tissue to another, supported by the observation that developmental compensation time in the mouse is not the same for each organ, as discussed above (Kojima et al, 2014).…”
Section: Size Control and Scalingmentioning
confidence: 90%
“…Importantly, this organoid formed without external scaffolding or mechanics, further demonstrating the innate ability of cells to self-generate functional multicellular structures. This approach was later adapted for making retinal tissue from human ESCs (hESCs) (Kuwahara et al, 2015). More recently, it was shown that human optic cup organoids engrafted onto injured eyes in primates continue to differentiate into a variety of retinal cell types, even creating synaptic contacts with the host (Shirai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…4B). Another aspect of the selforganizing property of retinal development from human PSCs was demonstrated more recently (Kuwahara et al, 2015), in which a specific stem cell niche called the retinal ciliary margin (RCM) (Agathocleous and Harris, 2009),which is located at the boundary of the NR and RPE, could be generated in vitro and displayed the potential to produce retinal progenitors, which in turn generate various retinal subtypes including photoreceptors (Fig. 4C).…”
Section: The Retinamentioning
confidence: 99%
“…4B) (Ader and Tanaka, 2014;Eiraku et al, 2011;Kuwahara et al, 2015;Nakano et al, 2012;Sasai et al, 2012). Initial retinal regional specification is achieved using culture with morphogen inhibitors such as Nodal for mouse PSCs and Wnt inhibitor for human PSCs, in the presence of basement membrane matrix components (Matrigel) (Nakano et al, 2012).…”
Section: The Retinamentioning
confidence: 99%
“…114,124 Formation of a ciliary margin stem cell niche in 3D optic vesicles was recently shown to expand the generation of the retinal progenitor cell population in vitro. 125 Further definition of conditions that expand progenitor populations committed to produce rod or cone photoreceptors would be very useful. A recent study demonstrated enrichment of ESC-derived cone photoreceptors using a new protocol inhibiting bone morphogenetic protein (BMP), transforming growth factor beta (TGFb), and Wnt signaling.…”
Section: Yield and Puritymentioning
confidence: 99%